Design of Rubbish as Pickup Object in The Maze Game Using Cellular Automata - Hanatar Adi Naluri; Purba Daru Kusuma (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
This educational game is perfect for children. So many kids nowadays actually play games that should be for adults. This is quite concerning because the age children should be the age of forming morals and in this study, the authors developed a maze game with the theme of manners or morals. In this game, the writer designed the pickup behavior of garbage objects using the cellular automata method. The results to be achieved in this study are to ensure the game can run smoothly without errors and pickup objects in the form of trash according to what was designed. In addition, with this maze game it is hoped that it can educate children so that morals or character are formed within them.